Loneliness, mental health and COVID-19 in the Spanish population - Berta Ausín (Escritos de Psicología - Psychological Writings, 2021)
The study aim was to assess the effects of the health emergency and the stay-at-home restrictions on loneliness variables in the Spanish population during the initial stage of COVID-19. A cross-sectional study was conducted through an online survey of 3480 people. From March 14, 2020, screening tests were used to evaluate sociodemographic and COVID-19-related data on loneliness, social support, the presence of mental health symptoms, discrimination, and spiritual well-being. Descriptive analyses were conducted and linear regression models were constructed. A negative association was found between loneliness and being older, being partnered, having children, being a university graduate, being retired or still working, having stronger religious beliefs, believing that information provided about the pandemic was adequate, having social support, and having self-compassion. Actions that promote social support and further studies on loneliness in groups of older people are needed to prevent the pandemic having a stronger impact on mental health and well-being.